2019
DOI: 10.1163/22134808-20191402
|View full text |Cite
|
Sign up to set email alerts
|

Multisensory Integration Is Modulated by Auditory Sound Frequency and Visual Spatial Frequency

Abstract: Accurate integration of auditory and visual information is essential for our ability to communicate with others. Previous studies have shown that the temporal discrepancies over which audiovisual speech stimuli will be integrated into a coherent percept are much wider than those typically observed for simple stimuli like beeps and flashes of light. However, our sensitivity to the low-level features of simple stimuli is not constant. We hypothesized that part of the enhanced integration of audiovisual speech ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The congruent pairs demonstrated significantly shorter reaction times in a speeded classification task. Green et al (2019) also demonstrated a crossmodal correspondence between a spatial frequency of a Gabor patch and the frequency of a tone. However, results…”
Section: Stimuli With Gabor Patches and Tonesmentioning
confidence: 86%
See 4 more Smart Citations
“…The congruent pairs demonstrated significantly shorter reaction times in a speeded classification task. Green et al (2019) also demonstrated a crossmodal correspondence between a spatial frequency of a Gabor patch and the frequency of a tone. However, results…”
Section: Stimuli With Gabor Patches and Tonesmentioning
confidence: 86%
“…Gabor patch and a sound also hold for longer stimuli remains unknown. Besides, the congruency of the stimuli was most often studied by assessing congruency effect, i.e., analysing the changes in response time or temporal window of integration in speed classification or search tasks (Evans and Treisman, 2010;Guzman-Martinez et al, 2012;Orchard-Mills et al, 2013a;Green et al, 2019). However, it is unknown whether stimuli examined in these studies are actually perceived as congruent or incongruent by participants, as no (in)congruency judgement was explicitly asked from participants.…”
Section: Studies With Longer Stimuli (> 1 Second)mentioning
confidence: 99%
See 3 more Smart Citations